The Economic & Ecological Potentials of Palm Oil Replanting in West Kalimantan: Case Study Ketapang Regency - Rosyadi, Rosyadi (Jurnal Social Economic of Agriculture, 2023)
Oil palm plantations are plantations that have the largest land and output in West Kalimantan, the output produced is not only palm oil, but will also produce other products such as production waste which can damage the environment. Replanting is carried out to reduce the resulting ecological impact, even so replanting carried out by smallholders/independent still leaves a lot of waste such as oil palm trunks and other biomass that has high economic potential. This study aims to estimate the potential waste in replanting activities, as well as the potential economic benefits that can be obtained by the process. Using quantitative analysis, with support of mathematical calculations that we have developed and based on data and empirical assumptions. The estimation results show that every year if replanting waste is processed into wood pellets it will provide an economic value of IDR 125,376,725,586.59 on independent plantations every year and are carbon neutral.